2022
DOI: 10.1155/2022/4042418
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Studies on Flowing Properties of Grouting Mortar Based on the Modified MPS Method

Abstract: Grouting mortar has widespread application in engineering because of the advantages of good durability, low cost, and environmental friendliness. To study the flowing properties of grouting mortar, laboratory minislump tests taking different rheological parameters of grouting mortar into consideration were conducted to obtain the flow time and flow pattern of grouting mortar. A modified MPS method (moving-particle semi-implicit method) introduced two sections of Bingham rheological, and segregation was propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…The precision of a simulation depends on the correct rheology and may require the use of the modified Bingham fluid model to explain the complex rheological behavior [20,21]. Soil is comparable to concrete or mortar in terms of its flowability, and thus, the flowability values of these materials are often used as a reference when determining the plastic viscosity value [22,23]. Aierken et al [22] explained the compatibility of bi-viscosity Bingham fluid in a mortar flow simulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The precision of a simulation depends on the correct rheology and may require the use of the modified Bingham fluid model to explain the complex rheological behavior [20,21]. Soil is comparable to concrete or mortar in terms of its flowability, and thus, the flowability values of these materials are often used as a reference when determining the plastic viscosity value [22,23]. Aierken et al [22] explained the compatibility of bi-viscosity Bingham fluid in a mortar flow simulation.…”
Section: Introductionmentioning
confidence: 99%
“…Soil is comparable to concrete or mortar in terms of its flowability, and thus, the flowability values of these materials are often used as a reference when determining the plastic viscosity value [22,23]. Aierken et al [22] explained the compatibility of bi-viscosity Bingham fluid in a mortar flow simulation. Shakya et al [23] suggested the extrapolation of the flow value vs. plastic viscosity, and the plastic…”
Section: Introductionmentioning
confidence: 99%